Developing discourse of renewal during a campus crisis. Issue 1 (2nd January 2017) - Boatwright, Brandon; Mazer, Joseph P.
Abstract : Course: This assignment is a unit activity designed for use in a skills-focused undergraduate public relations, organizational communication, or crisis communication course. Objective: The goal of this activity is to increase students' understanding of and ability to apply discourse of renewal in a crisis scenario. Students will work collaboratively to craft responses that affirm an organization's core values in light of a tragic event.